ENVIRONMENTAL FACTORS INFLUENCING CO2 EFFLUX IN BLACKWATER CONSERVATION AREA - Davis, Benjamin Michael; Mitchell, Jennifer L (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
As the global population burgeons, ecosystems face unprecedented challenges to sustain current levels of production. The preservation of sensitive ecosystems is now a critical imperative for the long-term viability of our planet. Among these, wetlands emerge as vital custodians of planetary health, covering approximately 6% of terrestrial land areas worldwide. In the United States alone, they span a vast 274 million acres, constituting 14% of the world’s total wetlands (Reddy & DeLaune, 2008). These ecosystems are estimated to sequester a staggering 350-535 gigatons of carbon (Mitra et al., 2005). However, the escalating global temperatures and erratic patterns of flooding and drought pose imminent threats to wetlands. There exists a looming risk of these lands desiccating, liberating colossal amounts of carbon back into the atmosphere. Rising temperatures have led to a reduction in both surface and groundwater levels, primarily due to heightened evapotranspiration. Consequently, the urgency to safeguard existing wetlands and pioneer innovative methods for the creation of new ones, capable of delivering commensurate services, has never been more apparent. This study significantly advances the understanding of wetlands’ pivotal role in mitigating global climate change. It sheds light on the critical interplay between soil moisture, temperature dynamics, and CO2 efflux, underscoring the urgency of comprehensive wetland conservation strategies.